2001
DOI: 10.1046/j.1526-4610.2001.111006011.x
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence of Recall Bias in Pediatric Headache: A Comparison of Questionnaire and Diary Data

Abstract: Recall errors occur when children are asked to report their headaches on a retrospective questionnaire. As compared to a prospective diary, pain complaints are evaluated more negatively on a questionnaire. Other factors such as age, depression, and headache severity influence the way children and adolescents recall their headaches. To minimize bias, the use of a diary when studying recurrent headache complaints in children is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
135
2
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(148 citation statements)
references
References 32 publications
8
135
2
3
Order By: Relevance
“…When revising the literature, Özge [8] reported published prevalences for headaches among schoolchildren from 5.9% to 82%. Further, different authors only found e.g., a poor agreement between headache frequency and intensity reported retrospectively in questionnaires and interviews compared with continuously registered data from diaries [27,35,36]. Also, the source of information plays an important role and contributes to the wide range of published results.…”
Section: Introductionmentioning
confidence: 99%
“…When revising the literature, Özge [8] reported published prevalences for headaches among schoolchildren from 5.9% to 82%. Further, different authors only found e.g., a poor agreement between headache frequency and intensity reported retrospectively in questionnaires and interviews compared with continuously registered data from diaries [27,35,36]. Also, the source of information plays an important role and contributes to the wide range of published results.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the prevalence of HA is 2 times greater among the 18.4% of youth aged 12 to 17 who have special health care needs (16.0%). 12 Studies suggest that many youth with HA experience HA on a weekly basis [13][14][15][16][17][18][19] and that they are 4 times more likely to miss an above routine number of school days and to have repeated emergency department visits. 20 Common conventional recommendations to prevent HA include improving lifestyle, particularly diet, sleep, and stress.…”
Section: Resultsmentioning
confidence: 99%
“…The overall prevalence of BP was 25% [95% CI [23][24][25][26][27][28] in the second survey year for children in grades 1-5 and 24% [95% CI [22][23][24][25][26][27] in survey year three for children in grades 2-6. Prevalence of "BP at least once" was thus similar from one survey year to the next.…”
Section: Participants and Text Messagesmentioning
confidence: 99%